PENGARUH ECONOMIC VALUE ADDED(EVA) DAN MARKET VALUEADDED(MVA) TERHADAP KINERJA PERUSAHAAN (ROA) PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA: Studi Empiris Perusahaan Perbankan Go Publicdi Bursa Efek Indonesia Periode Tahun 2020 (Prospect : Jurnal Manajemen dan Akuntansi, 2021)
The aim of this research is to determine Economic Value Added (EVA), Market Value Added (MVA) and Return On Assets (ROA) in banking companies listed on the IDX for the 2020 period. The data collection technique used in this research method is literature study. The population in this study was 43 companies. In this research, researchers carried out samples to represent the population using simple random sampling, with a sample of 23 samples. This research explores and analyzes the independent and dependent variables consisting of Economic Value Added/EVA (X1), Market Value Added/MVA (X2) and Company Performance / Return On Assets (Y) which will be analyzed using multiple correlation analysis techniques, multiple regression , t test, f test and determination coefficient. In this research, the regression test obtained the equation ` Y = 0.605 + 1.213 X1 –6.558 X2. Where the constant is 0.605, which means that if Economic Value Added (EVA) and MVA are fixed (or 0), then ROA is 0.605. And if X1 or Economic Value Added (EVA) increases by one unit while X2 or MVA remains constant (or 0), then ROA will increase by 1.213. And if X1 or Economic Value Added (EVA) remains (or 0) while X2 or MVA increases by one unit, then ROA will decrease by 6.558. In the t test for Economic Value Added (EVA) it is known that the t count is 0.934 and the t table is 172472. So t count < t table then ho is accepted, so that the poor Economic Value Added (EVA) makes Economic Value Added (EVA) does not affect ROA. Meanwhile, for MVA, it is known that t count is -1.382 and t table is 1.72472, so t count < t table so ho is accepted. So MVA partially has no effect on ROA. In ANOVA, the results obtained for Economic Value Added (EVA) and MVA in this study showed that the calculated f was 3.029 and the f table was 2.59. So f table < f count then ho is rejected, so that Economic Value Added (EVA) and MVA simultaneously influence ROA. The Adjusted R Square figure (correlation figure squared or 0.4822) is 0.156. The Adjusted R Square number is also called the Coefficient of Determination. The coefficient of determination is 0.156 or equal to 15.6%. This figure means that the 15.6% ROA that occurs can be explained using the Economic Value Added (EVA) and MVA variables. The remaining 84.4% (100% -15.6%) must be explained by other causal factors such as Net Profit Margin, Return on Sales and Debt to Equity Ratio.